The role of stimuli of life events and sleep quality in the incidence of acute low-tone sensorineural hearing loss - Xi He; Chao Huang; Fan Jiang; Hongli Lan; Yu Huang; Maojie Liu; Dan Lai (Frontiers in Neurology)
IntroductionIt is difficult to detect acute low-tone sensorineural hearing loss (ALHL) because of only low-frequency hearing loss and atypical early symptoms. The etiology of ALHL is still elusive, and psychosomatic factors influence deafness and tinnitus. Therefore, this study aimed to clarify the correlation between psychosomatic factors and the incidence of ALHL to facilitate the prevention of ALHL.MethodsPatients with stuffy ears and tinnitus who were admitted to the Outpatient Clinic of the Affiliated Hospital of Southwestern Medical University (Luzhou, China) from July 2020 to May 2023 were identified in this retrospective study. The general data, hearing screening form, the Life Event Scale, and the Pittsburgh Sleep Quality Index scale were employed to assess patients’ hearing levels and stimuli of psychosomatic symptoms. Finally, the correlation among the stimuli of life events, sleep quality, and ALHL was statistically analyzed.ResultsA total of 97 ALHL patients and 97 healthy participants were enrolled in the case group and control group, respectively. The two groups had no significant differences in general information (all p > 0.05). The amount of negative life event stimuli was significantly larger in ALHL patients than in the normal population (p = 0.000). Patients with ALHL had significantly poorer sleep quality than the healthy population (p = 0.000). There was a positive correlation between sleep quality and ALHL severity (250 Hz: r = 0.336, p = 0.001; 500 Hz: r = 0.299, p = 0.003), and a positive correlation between the stimuli of life events and sleep quality (r = 0.535, p = 0.000).DiscussionSleep quality was found to be closely associated with the degree of hearing loss in ALHL patients, and there was also a strong correlation between sleep quality and the stimuli of life events. Therefore, psychosomatic factors may play an important role in the occurrence of ALHL.